Scalar trajectories in design: The case of DIY cloth face masks during the COVID-19 pandemic. Issue 1 (23rd January 2023) - Botero, Andrea; Saad-Sulonen, Joanna
The article examines an artefact of everyday design – the Do-It-Yourself (DIY) cloth face mask employed against respiratory infections – to interrogate scale and scalar relationships. This lens reveals new perspectives on how practice-based design research can mobilize scale in more nuanced ways. The authors propose that DIY face masks, as artefacts of mundane design engagements both with material (cloth and thread) and with sharing of knowledge (about design, craft and practice), globally and within local networks and communities, direct our attention to scale as a matter of relations, engagements and emergent trajectories. Through empirically led exploration combined with approaching making as sensemaking, the article highlights the multiplicity of design artefacts emerging in DIY mask design spanning several scales and introduces the notion of scalar trajectories across multiple design engagements.